The effectiveness of nanotechnology toothbrush bristles in maintaining oral hygiene of children aged 9–12 years: a quasi-experimental - Parihala, Juan Dion; Fadilah, Rina Putri Noer; Endrowahyudi, Hartanto; Supriatna, Andi; Khairunnisa, Zahra (Padjadjaran Journal of Dentistry, 2026)
Introduction: Dental caries remains a common oral health problem among school-aged children and is associated with oral hygiene practices and plaque control. In Indonesia, its high prevalence highlights the need for effective preventive strategies. Conventional toothbrushes rely mainly on mechanical plaque removal, which may be limited in children due to variations in brushing technique. Recent developments have introduced nanotechnology in toothbrush bristles, where nanosilver is incorporated into the bristle material and has been reported to exhibit antibacterial and anti-biofilm properties that may support plaque control during brushing. However, evidence of its effectiveness in children remains limited. This study aimed to analyze the effectiveness of nanotechnology toothbrush bristles in maintaining oral hygiene among children aged 9–12 years. Methods: This study employed a quasi-experimental design with a control group pre-test and post-test approach. A total of 62 children aged 9–12 years were included: the experimental group using nanosilver-bristled toothbrushes (n=31) and the control group using conventional toothbrushes (n=31). All participants received the same toothbrushing instruction at baseline. Oral hygiene was assessed using the Patient Hygiene Performance (PHP) index on selected index teeth representing anterior and posterior sextants, measured at baseline and after a 21-day intervention. As the data were not normally distributed, the Wilcoxon signed-rank test and Mann–Whitney U test were used. Results: Baseline PHP scores were comparable between groups (p>0.05). After the intervention, the mean PHP score in the experimental group decreased from 3.87 ± 1.074 to 1.51 ± 1.040 (61.0% reduction; p<0.05). In the control group, the mean PHP score decreased from 3.38 ± 0.734 to 2.88 ± 0.799 (14.8% reduction; p<0.05). The reduction in PHP scores was significantly greater in the experimental group (p<0.05). Conclusion: Toothbrushes with nanosilver bristles were more effective than conventional toothbrushes in improving oral hygiene among children aged 9–12 years.